Effect of perceived career development and work-life balance to psychological well-being of lecturer - Meriam Esterina; Silvi, Mergana Septika; Desy Rahmawati (Penerbit Universiti Kebangsaan Malaysia, 2020)
The amount of work requirement that must be met by lecturers can cause stress and create discomfort feelings. Therefore, institutions need to pay attention to things that can reduce the psychological well-being of their lecturers so that they can comfortably work and give their best performance. This study aims to determine the effect of perceived career development and work-life balance to psychological well-being of lecturers. A total of 63 lecturers from P University became the sample of this study which was obtained by convenience sampling method. The measuring instrument used consists of the Perceived Career Development Scale, Work-Life Balance Scale, and Psychological Well-Being Scale. The analytical method used is multiple regression analysis technique and using SPSS 16. The results showed that there was no influence of perceived career development and work-life balance to psychological well-being of lecturers at P University (F = 3.471, p = 0.037, p> 0.05).